Improving the Glimepiride Efficacy in Type 2 Diabetes Treatment: A Review of the Potential Advantages and Disadvantages of Glimepiride as Hypoglycemic Oral Medication. - Gehad Abdelazeem Elshamy; Hany M El-Bassossy; Shimaa Elshazly; Nesreen Elkomy (Zagazig Journal of Pharmaceutical Sciences, 2025)
Type 2diabetes is a major health problem that affects the majority of advanced and developing countries at the same limit ,type 2 diabetes is characterized by insulin resistance which generated after metabolic syndrome induction due to weight gain and low physical activity ,also characterized by insufficiency of pancreatic beta cells and progressive destruction of those cells due to oxidative stress produced by permenant hyperglycemia and hyperlipidemia. The major concern of type 2 diabetes is its complications .Acute complications of type 2 diabetes are diabetic ketoacidosis , diabetic coma,hypoglycemia or hyperglycemia,chronic complications are divided into microvascular (retinopathy, nephropathy, and neuropathy) and macrovascular (ischemic heart disease, peripheral vascular disease, and cerebrovascular disease). Those complications act as a burden on health and economic organizations so finding a proper, available and safe medication was a great concern to many countries to reduce the load on economic and health organizations. There are many oral drug classes introduced for treating type 2 diabetes one of them is sulphonylurea .they act by secretagogue activity and the most commonly used drug of this class is glimepiride which is considered as the most effective and the safest one of them but it has some side effects like weight gain, hypoglycemia, and destruction of beta-cell after a short duration of reaching the maximal dose so many experimental and clinical trials are done to improve its safety profile.